Thermo-mechanical Behavior of C45 Steel over a Range of Temperatures and Loading Rates - Saffarini, Mohammad Hassan (2016)
A Master of Science thesis in Civil Engineering by Mohammad Hassan Saffarini entitled, "Thermo-mechanical Behavior of C45 Steel over a Range of Temperatures and Loading Rates," submitted in January 2016. Thesis advisor is Dr. Farid H. Abed. Soft and hard copy available.